The Role of Fungal Microbiome Components on the Adaptation to Salinity of Festuca rubra subsp. pruinosa - Pereira, Eric C.; Vazquez de Aldana, Beatriz R.; Arellano, Juan B.; Zabalgogeazcoa, Iñigo (Frontiers in Plant Science, 2021)
Festuca rubra subsp. pruinosa is a perennial grass that inhabits sea cliffs, a habitat where salinity and low nutrient availability occur. These plants have a rich fungal microbiome, and particularly common are their associations with Epichloë festucae in aboveground tissues, and with Fusarium oxysporum and Periconia macrospinosa in roots. In this study, we hypothesized that these fungi could affect the performance of Festuca rubra plants under salinity, being important complements for plant habitat adaptation. Two lines of Festuca rubra, each one consisting of Epichloë infected and Epichloë free clones were inoculated with the root endophytes (Fusarium oxysporum and Periconia macrospinosa) and subjected to a salinity treatment. Under salinity, plants symbiotic with Epichloë had lower Na+ content than non symbiotic plants, but this effect was not translated into plant growth. Periconia macrospinosa promoted leaf and root growth in the presence and absence of salinity, and Fusarium oxysporum promoted leaf and root growth in the presence and absence of salinity, plus a decrease in leaf Na+ content under salinity. The growth responses could be due to functions related to improved nutrient acquisition, while the reduction of Na+ content might be associated with salinity tolerance and plant survival in the long term. Each of these three components of the Festuca rubra core mycobiome contributed with different functions, which are beneficial and complementary for plant adaptation to its habitat in sea cliffs. Although our results do not support an obvious role of Epichloë itself in FRP salt tolerance, there is evidence that Epichloë can interact with root endophytes, affecting host plant performance.